ANTAGONISTIC EFFECT OF YEAST, ACETIC ACID BACTERIA AND MANGOSTEEN RIND EXTRACT ON AFLATOXIGENIC Aspergillus flavus IN UNFERMENTED COCOA BEANS - Nijma Nurfadila; Sutrisno Sutrisno; Usman Ahmad; Samsudin Samsudin (BIOTROPIA, 2021)
Yeasts and bacteria are two of common biocontrol agents to control mycotoxigenic fungi, meanwhile the mangosteen rind exract has xanthone and gartanin compounds for antioxidant, antiproliferation, antiinflammation, antimicrobial, and anticancer. The objectives of this research are to test the effects of yeasts, acetic acid bacteria (AAB), and mangosteen rind extract on the aflatoxigenic Aspergillus flavus growth and aflatoxin production in unfermented cocoa beans. Four yeast isolates, i.e. Issatchenkia orientalis (Io) BIO 211291, 286 and 288, and Endomyces fibuliger (Ef) BIO 132219; one bacteria isolate of Acetobacter aceti (Aa) FNCC0016; and mangosteen rind extract (MRE) were tested for their capabilities in inhibiting an aflatoxigenic A. flavus (Af) BIO 3361/747 growth using the well method (in vitro). Two yeast (Io BIO 211291 and 288) were combined with Aa and MRE in cocoa beans (in vivo). Aflatoxin production was analyzed using Thin Layer Chromathography (TLC). The result showed that interaction of Io BIO 211291 and 288, and Ef BIO 132219 on aflatoxigenic Af were interaction with inhibition zone ≥ 2 mm (type D), while the interaction type of Io BIO 211286 on Af were mutual intermingling growth, where both fungi grew into each other without any macroscopic sign of interaction (type A). The best treatment in agar media (in vitro) was Io BIO 211288 + Aa on Potato Dextrose Agar + 12 g/l MRE. The highest Io population was 5.88 log cfu/g on cocoa beans inoculated by Io BIO 211291 + MRE in 1 day after inoculation, while the highest A. aceti population was 4.74 log cfu/g on cocoa beans with Io BIO 211291 + BIO 211288 + Aa  in 3 days after inoculation. Two best treatments were Io BIO 211288 + Aa + MRE and Io BIO 211291 + BIO 211288 + Aa + MRE, because there were no A. flavus population since 3 until 11 days after inoculation. Aflatoxin in all samples treatment was lower than limit detection B1 (< 2.20 ppb),  B2 (< 3.50 ppb), (G1 < 0.54 ppb), dan (G2 < 1.00 ppb).